Functional Specificity of Cardiolipin Synthase Revealed by the Identification of a Cardiolipin Synthase CrCLS1 in Chlamydomonas reinhardtii - Hung, Chun-Hsien; Kobayashi, Koichi; Wada, Hajime; Nakamura, Yuki (Frontiers in Microbiology, 2016)
Phosphatidylglycerol (PG) and cardiolipin (CL) are two essential classes of phospholipid in plants and algae. Phosphatidylglycerophosphate synthase (PGPS) and cardiolipin synthase (CLS) involved in the biosynthesis of PG and CL belong to CDP-alcohol phosphotransferase and share overall amino acid sequence homology. However, it remains elusive whether PGPS and CLS are functionally distinct in vivo. Here, we report identification of a gene encoding CLS in Chlamydomonas reinhardtii, CrCLS1, and its functional compatibility. Whereas CrCLS1 did not complement the growth phenotype of a PGPS mutant of Synechocystis sp. PCC 6803, it rescued the temperature-sensitive growth phenotype, growth profile with different carbon sources, phospholipid composition and enzyme activity of ∆crd1, a CLS mutant of Saccharomyces cerevisiae. These results suggest that CrCLS1 encodes a functional CLS of C. reinhardtii as the first identified algal CLS, whose enzyme function is distinct from that of PGPSs from C. reinhardtii. Comparison of CDP-alcohol phosphotransferase motif between PGPS and CLS among different species revealed a possible additional motif that might define the substrate specificity of these closely related enzymes.